2021
DOI: 10.1371/journal.pone.0253158
|View full text |Cite
|
Sign up to set email alerts
|

Will land circulation sway “grain orientation”? The impact of rural land circulation on farmers’ agricultural planting structures

Abstract: This study calculates the effect of different types of land circulation on farmers’ decision-making regarding agricultural planting structure, using field survey data involving 1,120 households in Hubei province, China, and PSM (propensity score matching) and GPSM (general propensity score matching) methods. Results from PSM showed that land circulation could significantly increase farmers’ decisions to plant food crops, which confirms the positive effect of rural land circulation on the “grain orientation” of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Green agriculture is a crucial part of this global sustainable development blueprint [19]. Many nations have made reasonable attempts to realize green agriculture, including ecologically friendly farmland circulation emphasizing the maintenance of farmland quantities (see, e.g., the Conservation Reserve Program of the United States [20]; Common Agricultural Policy in the European Union [21]; Summer Fallow in Australia [22]; the Ecological Farming System of Farmland Circulation in China [23]) and measures aimed at maintaining the farmland quality, especially avoiding farmland pollution. There are numerous pollution sources in farmland, such as chemical fertilizers and pesticides [24,25], agriculture film [26], municipal refuse [27], and industrial sewage [28].…”
Section: Research Background 21 Green Agriculture and Ecological Fert...mentioning
confidence: 99%
See 1 more Smart Citation
“…Green agriculture is a crucial part of this global sustainable development blueprint [19]. Many nations have made reasonable attempts to realize green agriculture, including ecologically friendly farmland circulation emphasizing the maintenance of farmland quantities (see, e.g., the Conservation Reserve Program of the United States [20]; Common Agricultural Policy in the European Union [21]; Summer Fallow in Australia [22]; the Ecological Farming System of Farmland Circulation in China [23]) and measures aimed at maintaining the farmland quality, especially avoiding farmland pollution. There are numerous pollution sources in farmland, such as chemical fertilizers and pesticides [24,25], agriculture film [26], municipal refuse [27], and industrial sewage [28].…”
Section: Research Background 21 Green Agriculture and Ecological Fert...mentioning
confidence: 99%
“…First, green agriculture is a major direction for Chinese agriculture development and the solution for the problems facing China, such as deteriorating land quality and land yields. The Chinese government has focused on maintaining the quantity of farmland (e.g., through agriculture land circulation programs [23]). It is not until recent years that the Chinese government has begun to emphasize the significance of maintaining farmland quality in the face of significant soil fertility decline, pollution, and potential risks to food security and sustainability development, and has thus devoted attention to exploring policies for farmland quality maintenance.…”
Section: Research Samplementioning
confidence: 99%
“…In combination with the research basis of its predecessors, we used previous research results to measure the level of non-grain production by the proportion of non-grain crops planted to the total area of crops sown, where non-grain crops are based on relevant Chinese laws and regulations and are non-grain crops other than cereals, soybeans, and tuber crops [ 15 , 48 , 49 ]. The formula can be written as follows: …”
Section: Methodsmentioning
confidence: 99%
“…Land and labor are important factors of production for farmers, a relationship that many scholars have thoroughly discussed, but more scholars focus on the analysis of non-farm employment as an influence of land transfer [ 1 , 2 , 3 ], and only a few scholars analyze the impact of land transfer on non-agricultural employment of rural households [ 4 , 5 ], mainly from the perspective of the evolution of the land system and the development of the transfer market [ 6 ]. The non-farm employment of rural labor force is closely related to the rural land system [ 7 ], as the adjustment of contracted land management rights will reduce farmers’ expectation of the stability of land rights [ 8 , 9 ], make farmers divest their possession of land use rights and turn to invest more labor force in the field of non-farm production [ 10 , 11 , 12 ]. Subsequently, many scholars found that land right confirmation can increase the expectation of pure farming farmers on the stability of land property rights and eliminate their concerns after land transfer [ 13 , 14 , 15 ]; moreover, the land scale effect will improve agricultural production efficiency [ 16 ], thus promoting the employment of rural labor force [ 17 ].…”
Section: Literature Review and Theoretical Mechanismsmentioning
confidence: 99%